O corpo ciborgue na publicidade de moda: o papel do jeans - Agustoni, Marina (2011)
The intention of this research is to analyze the increasing mechanization of bodies in fashion ads in the last three years and, in parallel, the part of jeans in the process. It's also to examine the influence of technology on fashion and its corollary: the cyborg body. So the objects of the research are fashion, fashion advertising, jeans, cyborg and the cyborgzation. The selected corpus is composed of clippings in the press and digital media, and covers the Vogue, Iguatemi Shopping, Marie Claire, as well as UOL fashion catalog. The theorical reference is Walter Benjamin's reflections about the "inorganic sex-appeal" and the rereading of this concept in the work of Massimo Canevacci. Combined with this theorical main base there are Lucia Santaella main reflections on the contemporary body and those of authors such Anne Hollander, Gilles Lipovetsky, Diane Crane, among other fashion and clothes experts. Methodologically, the research is documentary and bibliographical. The hypothesis is that fashion is not the only villain of the human figure cyborgzation, fashion absorbs and spreads through the trend, using new technologies as tools that emerge, thereby cyborgzation of the human figure is not only responsibility of fashion, is a reflection of an increasingly technological society that increasingly understands the person just like a body, like a puppet. This is an essay about how the jeans and the new technologies allied with fashion are transforming the human image, standardizing it and subjecting it to a level of dehumanization; about how it is understood and seen this new man who crossed the borders of skin and now is a mutation betwen the sensitive and the sensors, between the body and its mechanical extensions; about this cyborg body, who contrasts in fashion advertising in recent years